2010
DOI: 10.1158/0008-5472.can-10-1318
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetically Deregulated microRNA-375 Is Involved in a Positive Feedback Loop with Estrogen Receptor α in Breast Cancer Cells

Abstract: Estrogen receptor α (ERα) upregulation causes abnormal cell proliferation in about two thirds of breast cancers, yet understanding of the underlying mechanisms remains incomplete. Here, we show that high expression of the microRNA miR-375 in ERα-positive breast cell lines is a key driver of their proliferation. miR-375 overexpression was caused by loss of epigenetic marks including H3K9me2 and local DNA hypomethylation, dissociation of the transcriptional repressor CTCF from the miR-375 promoter, and interacti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
199
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 266 publications
(222 citation statements)
references
References 48 publications
19
199
1
Order By: Relevance
“…Although several studies did not notice an upregulation of miR-375 in prostate carcinoma samples, various studies observed increased levels of this miRNA in prostate cancer serum samples (44,45). Publications confirm that miR-375 is downregulated in other cancer types such as cervical, lung, or head and neck carcinoma, as well as glioma (46)(47)(48)(49)(50) but upregulated in breast carcinoma (51). Likewise, miR-15a was previously shown to be downregulated in metastasizing prostate carcinoma (18).…”
Section: Discussionmentioning
confidence: 80%
“…Although several studies did not notice an upregulation of miR-375 in prostate carcinoma samples, various studies observed increased levels of this miRNA in prostate cancer serum samples (44,45). Publications confirm that miR-375 is downregulated in other cancer types such as cervical, lung, or head and neck carcinoma, as well as glioma (46)(47)(48)(49)(50) but upregulated in breast carcinoma (51). Likewise, miR-15a was previously shown to be downregulated in metastasizing prostate carcinoma (18).…”
Section: Discussionmentioning
confidence: 80%
“…In breast cancer, higher expression of miR-375 in ERa-positive breast cell lines was shown to influence cell proliferation, and miR-375 overexpression caused loss of epigenetic marks including H3K9me2 and local DNA hypomethylation. Inhibition of miR-375 in ERa-positive MCF-7 cells reduced both ERa activation and cell proliferation [35]. In gastric cancer, miRNA-375 was found to be the most down-regulated miRNA, and ectopic expression of miRNA-375 in gastric carcinoma cells markedly reduced cell viability by a mechanism involving the caspase-mediated apoptosis pathway [37].…”
Section: Discussionmentioning
confidence: 96%
“…Recently, miR-375 hypermethylation was reported in breast cancer and gastric cancer [35,36]. In breast cancer, higher expression of miR-375 in ERa-positive breast cell lines was shown to influence cell proliferation, and miR-375 overexpression caused loss of epigenetic marks including H3K9me2 and local DNA hypomethylation.…”
Section: Discussionmentioning
confidence: 99%
“…We found elevated miR-375 levels in SBNETs, which is also more often downregulated in cancers. However, high expression of miR-375 has been seen in ERα-positive breast cell lines and it is a key driver of their proliferation (de Souza Rocha Simonini et al 2010).…”
Section: Global Mirna Profiling Reveals a Signature Specific For Smalmentioning
confidence: 99%